Correlation between oxygen evolution reaction activity and surface compositional evolution in epitaxial La0.5Sr0.5Ni1−xFexO3−δ thin films. Issue 3 (3rd January 2023) - Adiga, Prajwal; Wang, Le; Wong, Cindy; Matthews, Bethany E.; Bowden, Mark E.; Spurgeon, Steven R.; Sterbinsky, George E.; Blum, Monika; Choi, Min-Ju; Tao, Jinhui; Kaspar, Tiffany C.; Chambers, Scott A.; et al.
Abstract : A Ni–Fe based perovskite oxide catalyzes the oxygen evolution reaction (OER), coupled with changes in local composition and structure identified by virtue of an epitaxial thin film geometry. Abstract : Water electrolysis can use renewable electricity to produce green hydrogen, a portable fuel and sustainable chemical precursor. Improving electrolyzer efficiency hinges on the activity of the oxygen evolution reaction (OER) catalyst. Earth-abundant, ABO3 -type perovskite oxides offer great compositional, structural, and electronic tunability, with previous studies showing compositional substitution can increase the OER activity drastically. However, the relationship between the tailored bulk composition and that of the surface, where OER occurs, remains unclear. Here, we study the effects of electrochemical cycling on the OER activity of La0.5 Sr0.5 Ni1− x Fe x O3− δ ( x = 0–0.5) epitaxial films grown by oxide molecular beam epitaxy as a model Sr-containing perovskite oxide. Electrochemical testing and surface-sensitive spectroscopic analyses show Ni segregation, which is affected by electrochemical history, along with surface amorphization, coupled with changes in OER activity. Our findings highlight the importance of surface composition and electrochemical cycling conditions in understanding OER performance, suggesting common motifs of the active surface with high surface area systems.